Comparative Study of the Potential of the Halal Industry in Developed Countries vs Developing Countries - Lubis, Firsty Ramadhona Amalia; R.G.P, Muhammad Arsy; Yuandita, Risya (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this study is to compare the halal industry in developed countries with developing countries. By using research indicators of Muslim Tourist Visits, Halal Industry Market Area, Halal Certification, and Supply Chain Management. Countries that are the object of research are Japan and Singapore as developed countries, Indonesia and Thailand as developing countries. This study uses a qualitative descriptive method with reference to secondary data and previous research related to the halal industry in developed and developing countries. The results of the study show that Japan and Singapore as objects of developed countries still have superior values ??in the development of the halal industry. Where in Muslim minority countries such as Japan and Singapore have considerable potential in the halal industry sector which is able to support halal tourism activities with the guarantee of adequate Islamic facilities, when compared to Indonesia and Thailand as developing countries. Even though Indonesia is a country with a Muslim majority population, this has not shown that the halal industry in Muslim countries cannot necessarily develop well. As for the results of the wide market, developing countries have superior results but the market value only covers the range of providing the halal industry in the country, especially in halal food.